Comparison of the predictive utility of Revised Trauma Score,Emergency Trauma Score, and Glasgow Coma Scale-Age-Pressurescores for emergency department mortality in multiple traumapatients - (:unkn) unknown (My University, 2020)
Objective: In this study, we aimed to compare the utility of Revised Trauma Score (RTS), Glasgow Coma Scale, Age, and SystolicBlood Pressure (GAP) scores, and Emergency Trauma Score (EMTRAS) in multiple trauma patients for the prediction of mortalityin the emergency department (ED).Materials and Methods: In this observational diagnostic accuracy study, a consecutive convenience sample of all adult patients (olderthan 16 years) with multiple trauma (injuries confined to at least two body regions) admitted to the trauma bay of the ED during theshifts of the researchers was used. Presence of ED mortality was recorded, and RTS, EMTRAS, and GAP scores were calculated at theanalysis stage of this study.Results: The study sample included 279 multiple trauma patients. Of the 279 patients, 13 (4.7%) died in the ED. Among the 266patients who survived to hospital admission, 3 were lost to-follow-up (foreigner patients). In the following 30 days, 28 more patientswere lost, 23 in the Intensive Care Unit (ICU) (23/62, 37.1%), 4 in the wards (4/131, 3.1%), and 1 after discharge (1/73, 0.1%). Theprognostic accuracies (AUC) of RTS, EMTRAS, and GAP were 0.92, 0.94, and 0.93, respectively, for ED mortality.Conclusion: In this study, all trauma scores performed similar in the ED for the prediction of ED mortality